Edukasi Pengetahuan Masyarakat Melalui Upaya Sanitasi Lingkungan Tentang Pencegahan Leptospirosis Daerah Rawan Banjir - Erlani, Erlani; Sulasmi, Sulasmi; Nurhaidah, Nurhaidah (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Leptospirosis also known as Well's disease, is an acute infection that can affect humans and animals and is classified as a zoonotic disease. This disease is caused by bacteria from the genus Leptospira, which are commonly found in rodents. Cases of leptospirosis in humans generally occur during the rainy season with high rainfall that often causes flooding, both in urban and rural areas. This disease also tends to appear in areas with poor sanitation, low implementation of clean and healthy living behaviors, and a high population of rats carrying Leptospira bacteria in the environment. The problem in the target locations is the lack of public knowledge regarding environmental sanitation efforts and leptospirosis prevention. Educational activities are carried out in two areas: Banta-bantang and Manggala. The solution to be provided at the target locations is counseling on environmental sanitation efforts, including how to control rats both physically and chemically. Based on the implementation plan, the external targets include submitting a national journal, creating a video of the activity implementation and intellectual property rights (HAKI), while the achievement targets in community service are implementation achievement targets. The target for implementation is that 80% of the community understands efforts to prevent leptospirosis 80%, the community understands rat control 80% and education on making rat traps 80%. Keywords: Education, Leptospirosis